Adopting Hands-Off Approaches to Activism: Examining PSTs' Experiences Navigating Visibility and Vulnerability as Teacher Activists. (November 2021) - Cook, Mike P.
This case study examines six English Language Arts (ELA) preservice teachers (PSTs) and the ways they recognize injustice and inequity in education, plan for addressing such issues, and engage as teacher-activists toward impacting the issues they recognize. This research was guided by the following two questions: In what ways do ELA PSTs use their own recognition of educational injustice/inequity to foster discussions of methods for addressing such issues? How do PSTs engage in the agentive work of activists to impact those issues? Findings point to the ways in which PSTs adopt hands-off approaches to activism, or what I theorize as passive activism, where they, perhaps unconsciously, shield and distance themselves from the visibility and vulnerability that accompanies activist work. After a discussion of findings, I offer implications for the field and the ways teacher educators can better scaffold PSTs as they work to "do" the work of activists both inside and outside their classrooms.